2005
DOI: 10.1007/bf02708364
|View full text |Cite
|
Sign up to set email alerts
|

Bottlenecks in the prediction of regioselectivity of [4 + 2] cycloaddition reactions: An assessment of reactivity descriptors

Abstract: B3LYP/6-31G(d) calculations were performed to obtain all the transition states and products for the 128 distinct reaction channels of Diels-Alder reactions by taking all possible combinations from a series of dienes (1N-a, 1N-b, 2N, 1P-a, 1P-b, 2P, 1O, 1S) and dienophiles (NE, PE, OE, SE, AE, OHE, MeE, CNE). The predictive ability of the values to gauge the regioselectivity of the putative [4 + 2] cycloaddition reactions is analysed. No correlation is obtained between the reaction energies and activation energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 14 publications
0
14
0
2
Order By: Relevance
“…[55] In conclusion of this section, we note that Gayatri and Sastry have assessed the performance of DFT descriptors for 64 Diels-Alder reactions shown in Scheme 9 for predicting regioselectivity. [56] Using Fukui function matching from B3LYP calculations, 53 of 64 reactions could be rationalized by this approach. This highlights the potential broad applicability of DFT descriptors to predict reactivity and selectivity, but also the approximate nature of these descriptors.…”
Section: Conceptual Density Functional Theory (Dft) and Hard And Softmentioning
confidence: 99%
“…[55] In conclusion of this section, we note that Gayatri and Sastry have assessed the performance of DFT descriptors for 64 Diels-Alder reactions shown in Scheme 9 for predicting regioselectivity. [56] Using Fukui function matching from B3LYP calculations, 53 of 64 reactions could be rationalized by this approach. This highlights the potential broad applicability of DFT descriptors to predict reactivity and selectivity, but also the approximate nature of these descriptors.…”
Section: Conceptual Density Functional Theory (Dft) and Hard And Softmentioning
confidence: 99%
“…To support this choice and before studying the mechanism from a theoretical point of view, we analyzed the global electrophilic indices of 1f, 2a and 2b through conceptual DFT descriptors. [37,39,40] The results of this theoretical investigation have been reported in Table 3. Table 3.…”
Section: Entrymentioning
confidence: 96%
“…0.048) due to a destabilizing entropy effect. [37] Taking advantage of the results reported by De Lucchi and Pasquato [38] on the reactivity of sulfones in the DielsAlder reaction, the next step in our studies was to consider a new reaction pathway in which the electron-demanding nature of the dienophile was increased by adding an extra sulfone group to the scaffold. To support this choice and before studying the mechanism from a theoretical point of view, we analyzed the global electrophilic indices of 1f, 2a and 2b through conceptual DFT descriptors.…”
Section: Entrymentioning
confidence: 98%
See 1 more Smart Citation
“…[3,4] These conceptual DFT-based descriptors have been successfully applied to interpret reactivity or site-selectivity in different cycloaddition reactions. [5] For the reactions shown in Scheme 1, for instance, we demonstrated that the local electrophilicity (ω k ) and nucleophilicity (N k ) can be used to explain the observed regioselectivity.…”
Section: Introductionmentioning
confidence: 99%